2022
DOI: 10.3389/finsc.2022.1025193
|View full text |Cite
|
Sign up to set email alerts
|

Development of rearing methodology for the invasive Spotted Lanternfly, Lycorma delicatula (Hemiptera: Fulgoridae)

Abstract: Lycorma delicatula, White (Hemiptera: Fulgoridae), spotted lanternfly, is a univoltine, phloem-feeding, polyphagous and invasive insect in the USA. Although a primary host for this species is Ailanthus altissima, tree of heaven, L. delicatula also feeds on a wide range of hosts important to the USA including cultivated grapevines. Due to the need for classical or augmentative biological control programs to reduce impacts of L. delicatula across invaded areas, we developed a laboratory-based rearing protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…As such, the 30 cm tall, younger plant material used in this greenhouse study may not have contained sufficient phloem volume for the prodigious feeding behavior of adults and affected their survival, though we tried to compensate for this possibility with frequent plant replacements. Although previous greenhouse studies have shown that SLF can reproduce on these smaller trees (8), here, only one female was mated and none had fully developed ovaries despite some adults living in excess of 6 weeks. This may be due in part to the conditions under which these SLF were held.…”
Section: Discussionmentioning
confidence: 85%
“…As such, the 30 cm tall, younger plant material used in this greenhouse study may not have contained sufficient phloem volume for the prodigious feeding behavior of adults and affected their survival, though we tried to compensate for this possibility with frequent plant replacements. Although previous greenhouse studies have shown that SLF can reproduce on these smaller trees (8), here, only one female was mated and none had fully developed ovaries despite some adults living in excess of 6 weeks. This may be due in part to the conditions under which these SLF were held.…”
Section: Discussionmentioning
confidence: 85%
“…And while L. delicatula is observed on V. riparia in natural habitats, when it was included as a host along with Ailanthus altissima (Mill.) Swingle (Sapindales: Simaroubaceae) in a rearing study, its presence provide strong survivorship to the adult stage, but not at a greater level than a diet of A. altissima alone (Nixon et al 2022a). In South Korea, common host plants include several members of the Vitaceae family (Park et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a rearing procedure for L. delicatula was developed. This methodology requires both suitable plant material, namely A. altissima plants and logs, and controlled environmental conditions for successful rearing in greenhouses or growth chambers (Nixon et al 2022). While this approach does generate both egg masses and nymphs, there may be a possibility of using egg masses collected from nature as a source for rearing biological control agents.…”
mentioning
confidence: 99%
“…High densities of egg masses have been recorded in the field (up to 75 egg masses per m 2 ) on natural host substrates (Liu 2019a; Liu & Hunter 2021). However, removal from these host substrates requires a great deal of time and careful handling (Nixon et al 2022) because egg masses become brittle as the winter season progresses, with the protective waxy coating flaking away and exposing egg masses to potential damage or dislodgement when removed from the substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation